Trail activity of ants (Hymenoptera, Formicidae) at different habitat structure - Stukalyuk, Stanislav; Akhmedov, Ascar; Kosiuk, Nataly (Penerbit Universiti Kebangsaan Malaysia, 2022)
and in 2019-2021 at the city of Kyiv in the region of Carpathians, Ukraine and in the city of Tashkent in Uzbekistan. The study covered natural (forest, meadow, steppe), suburban (alleys and tree planting) and urban habitats (tree planting along streets and roads, botanical gardens). The average number of workers on the trails per 2 minutes (activity) are obtained for each of the 21 dominant species of ants. Urbanized habitats are favorable for some ant species (Crematogaster subdentata and Lasius neglectus - invasive or native species, depending on the region, Dolichoderus quadripunctatus - native species), it is reflected in the maximum rates of activity on the trails. In urbanized habitat there are about 200-800 individuals of ants that can be observed on the trails, it is equal to or greater than the activity for other ant species in natural habitats (100-400 individuals per 2 minutes). In the primary range (Uzbekistan), activity indicators on trails in native species C. subdentata and L. neglectus are equal or lower than those in the secondary range (Crimea, Kyiv city, Ukraine). The maximum activity of L. neglectus on trails in urbanized habitats is in Tashkent city, less in Crimea (M-W test, Tashkent vs Crimea, P≤0.001), and in Kyiv city (Tashkent vs Kyiv, P≤0.001). For C. subdentata, the maximum activity in the conditions of Tashkent, less activity - in natural habitats (tugai forests) (Tashkent vs tugai, P≤0.001). The presence of permanent foraging trails indicates the dominant status of the ant species. The amount of traffic on the trails can vary greatly in different habitats.